NY AG ends Emergent's exclusivity for Narcan nasal spray. Issue 2 (10th January 2020) - Knopf, Alison
Abstract : Narcan, the lifesaving opioid overdose reversal drug, has been the only naloxone spray allowed on the market due to an exclusivity agreement between the pharmaceutical company that owns it — Emergent BioSolutions — and the company that makes the spray device. This deal is ending thanks to New York Attorney General Letitia James, who has made it possible, via an agreement with Emergent, for other companies to use the patented, proprietary spray technology. Emergent, which bought Adapt, the creator of Narcan, will have to renegotiate these terms, James announced on Jan. 2. "Given the tragic, devastating effects of the opioid crisis, and the urgent need for additional drugs for the emergency treatment of opioid overdoses, my office will do whatever possible to ensure that there are no unnecessary impediments to the development of additional lifesaving opioid overdose reversal drugs, " she said. "I'm proud to announce that, starting today, additional companies will be able to gain access to these nasal spray devices. With more companies able to access this easy‐to‐use technology, our hope is that we can reduce the number of opioid overdose deaths across New York and this nation and save millions of additional lives." A little history here: Adapt Pharma launched Narcan in February 2016, a year before the State Targeted Response (STR) grants were issued. Narcan is patented, but naloxone had been used for decades in the emergency treatment of opioid overdoses, by first responders and medical workers. In October 2018, in the middle of the lucrative STR (which no longer had to be 80% treatment) and State Opioid Response funding cycles, Emergent bought Adapt — for Narcan. Adapt had already entered into the contract with the nasal spray device manufacturer. Other pharmaceutical companies had been trying to develop a nalmefene overdose reversal drug using the device.